Agroecological break out: Legumes, crop diversification and the regenerative futures of UK agriculture. (December 2021) - Cusworth, George; Garnett, Tara; Lorimer, Jamie
Abstract: This paper reviews the shifting fate of legumes in UK agriculture. Legumes were once a common part of crop rotations, providing food and feed, while enhancing soil fertility and enabling pest control. During the 20th century, UK arable management became predicated on minimally diverse crop rotations, dependent on artificial fertilisers and pesticides. Legumes were locked out of food and farming. Existing research has identified the drivers of this lock-in. Whilst this intensive model increased crop yields, there are growing concerns around its greenhouse gas emissions and impacts on soil health and biodiversity. In response, there is a resurgence of interest in legumes as a solution to these problems, as part of a wider shift towards agroecological management. This analysis draws on interviews with different actors in the UK agricultural sector to present a Multi-Level Perspective analysis of the drivers and characteristics of this transition - what we term agroecological break-out. It describes how macro-level economic changes (a growing market for plant-based proteins) and political transitions (a focus on public goods subsidisation) are combining with shifting agricultural attitudes (such as concerns around soil health, and the prioritisation of multi-annual profitability over annual yields) to increase the attractiveness of crop diversification and legume cropping. These changes open space for micro-level innovations by private, public, and civil society actors to disrupt the meso-level status quo of minimally diverse crop rotations. The conclusion maps the different forms and trajectories of this break-out and reflects on their implications for the future of food and farming in the UK. Highlights: Lock in of intensive agricultural management beginning to loosen. Multi-level analysis is used to show signs of emergent 'agroecological breakout'. Public goods policies and consumer preferences creating conditions for transition. Growing industry interest in soil health and regenerative practices. Great potential for use of legumes to diversify crop rotations in UK.